The association between cumulative adverse childhood experiences and ultra-processed food addiction is moderated by substance use disorder history among adults seeking outpatient nutrition counseling - Wiss, David A.; Tran, Celine D.; LaFata, Erica M. (Frontiers in Psychiatry, 2025)
Adverse childhood experiences (ACEs), such as childhood maltreatment and household dysfunction, are positively linked to substance use disorders (SUD), weight loss efforts, and maladaptive eating behaviors, including ultra-processed food addiction (UPFA) and eating disorder (ED) symptoms. However, the differential association of ACEs with UPFA by lifetime SUD history and ACEs with EDs by weight suppression— the discrepancy between an individual’s highest and current weight/BMI in adulthood— have not been examined. Using logistic regression and marginal effects analysis, this cross-sectional study aimed to assess (1) cumulative ACEs as a risk factor for screening positive for UPFA and EDs, (2) lifetime SUD history as a moderator of the ACE-UPFA relationship, and (3) weight suppression as a moderator of the ACE-ED relationship. Among 287 adults presenting to a private practice offering nutrition counseling for EDs and SUD recovery, the presence of 4 or more ACEs (compared to <4 ACEs) significantly increased the odds of UPFA-positive screens (OR=1.99; CI=1.19-3.35; p=0.01) but not ED-positive screens (OR=1.36; CI=0.80-2.30, p=0.25). Additionally, the interaction between ACEs and SUD was significant to the UPFA outcome (p<0.01). Those with a self-reported lifetime history of SUD exhibited an increased probability of UPFA-positive screens in the presence of 4 or more ACEs. Meanwhile, the probability of UPFA-positive screens remained unchanged among those who did not report a lifetime SUD history. Cumulative ACEs did not significantly predict ED-positive screens, and the ACE-weight suppression interaction did not meet the threshold for significance. Overall findings underscore the cross-vulnerability between addictive behaviors and the potential importance of integrating nutrition interventions in addiction treatment for those with ACEs.